Bacterinas comerciais falharam em induzir resposta imune humoral em camundongos contra alguns fatores de patogenicidade de Mycoplasma hyopneumoniae - Fisch, Andressa (2014)
Enzootic Pneumoniae (EP), caused by Mycoplasma hyopneumoniae, generates significant economic losses to the pig industry worldwide. The currently available vaccines confer partial protection against the EP and the development of new vaccine strategies have proven necessary. In this paper, humoral immune response in mice of six comercial bacterins against sexteen recombinant antigens previously characterized of M. hyopneumoniae was evaluated by indirect ELISA. Seroconversion Seroconversion was used to determine biologically significant reactivity. The antigen MHP_0067 was recognized by sera from one inoculated group. The antigens MHP_0513 and MHP_0580 were recognized by sera from four inoculated groups each. For other antigens, not seroconversion was detected. Identify potentially protective antigens underexpressed in these vaccines and associate them with conventional vaccination may promote increased levels of protection. These antigens are potential targets for the composition of a recombinant subunit vaccine associated with the commercial vaccine.